2010
DOI: 10.1182/blood-2009-10-246967
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Gfi1 regulates G-CSF signaling and neutrophil development through the Ras activator RasGRP1

Abstract: The transcription factor growth factor independence 1 (Gfi1) and the growth factor granulocyte colony-stimulating factor (G-CSF) are individually essential for neutrophil differentiation from myeloid progenitors. Here, we provide evidence that the functions of Gfi1 and G-CSF are linked in the regulation of granulopoiesis. We report that Gfi1 promotes the expression of Ras guanine nucleotide releasing protein 1 (RasGRP1), an exchange factor that activates Ras, and that RasGRP1 is required for G-CSF signaling th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Furthermore, Gfi‐1‐ knockout mice exhibit abnormal granulocytopoiesis with the absence of phenotypically mature neutrophils and loss of primary but not secondary granule expression in the neutrophilic lineages in the circulation . Gfi‐1 has also been shown to regulate the G‐CSF/GCSF‐R signaling by activating the Ras/MEK/Erk signaling pathway, ultimately contributing to the G‐CSF–induced neutrophil differentiation . Another important TF in neutrophil terminal differentiation is the lymphoid enhancer factor‐1 (Lef‐1), which is highly expressed in neutrophil progenitors.…”
Section: Granulocytopoiesismentioning
confidence: 99%
“…Furthermore, Gfi‐1‐ knockout mice exhibit abnormal granulocytopoiesis with the absence of phenotypically mature neutrophils and loss of primary but not secondary granule expression in the neutrophilic lineages in the circulation . Gfi‐1 has also been shown to regulate the G‐CSF/GCSF‐R signaling by activating the Ras/MEK/Erk signaling pathway, ultimately contributing to the G‐CSF–induced neutrophil differentiation . Another important TF in neutrophil terminal differentiation is the lymphoid enhancer factor‐1 (Lef‐1), which is highly expressed in neutrophil progenitors.…”
Section: Granulocytopoiesismentioning
confidence: 99%
“…5) (Diaz-Flores et al, 2013). A second report suggested that RasGRP1 couples to a related cytokine, G-CSF, to induce phospho-ERK that is important for neutrophil development (de la Luz Sierra et al, 2010). More recently, our group demonstrated that IL-7-induced RasGTP is RasGRP1-dependent in T cell leukemic cells (Hartzell et al, 2013).…”
Section: Multiple Receptor Systems Couple To Rasgrp Proteinsmentioning
confidence: 99%
“…A candidate regulator is a transcription factor Gfi1. It has been shown that Gfi1 knockout mice have deficiency in RasGRP1 mRNA and protein levels (de la Luz Sierra et al, 2010). Interestingly, a recent report by the Moroy group demonstrated that Gfi1 mRNA levels are increased in a subset of human T-ALL patients, which had a Notch1-like gene expression signature (Khandanpour et al, 2013).…”
Section: A Special Role For Rasgrp1; Expression or Biochemical Features?mentioning
confidence: 99%
“…Myeloid precursors from Gfi-1−/− mice are unable to differentiate into mature neutrophils in vitro , but instead give rise to atypical monocytes. In contrast, overexpression of Gfi-1 accelerates neutrophilic differentiation at the expense of monocytic differentiation (10, 11). These data reveal a critical role of Gfi-1 during early myeloid development i.e., promotion of neutrophilic differentiation in an instructive manner and suppression of the monocytic development.…”
Section: Introductionmentioning
confidence: 99%